IMPLEMENTATION OF PROFESSIONALISM OF TEACHER AND FORMATION OF CHARACTER IN PRIMARY SCHOOL STUDENTS - Yulia Palupi (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2016)
Characters can be interpreted as a default, heart, soul, personality, character, behavior, per-sonality, character, character, temperament, and character of the individual. Characters here are marked and focused on Applying the values of kindness in action and behavior. A professional teacher is a person skilled in the art that have the academic knowledge skills, social skills, spiritual kecakakapan can deliver their students in achieving academic goals and a destination in pengembangan personality noble character. Character education is meant is a noble character and is expected to be developed in self-learners. In this case the character building of students leads to the understanding of how to develop learners in primary schools so as to have a personality, behavior, nature, character, and character is noble that leads to a series of attitudes, behavior, motivation, and skills that meet the standards of values and norms dijunjung high and must be obeyed.